2016
DOI: 10.1007/s00383-016-3948-4
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of recto-prostatic and recto-bulbar anorectal malformations

Abstract: Technical outcomes appear to be similar based on imaging studies, but FCES-assessed functional outcomes appear to favor LAARP for treatment of both RPF and RBF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 18 publications
0
32
0
Order By: Relevance
“…Two studies [21, 28] reported longer operative time of LAARP compared with that of the PSARP group (P = 0.13, P<0.001, respectively); while two studies [24, 27] were in the contrary (P>0.05, P<0.01, respectively); and one study [22] reported the two groups had the same operative time (P = 0.92) (Table 2). Therefore, the result of operative time was inconclusive.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Two studies [21, 28] reported longer operative time of LAARP compared with that of the PSARP group (P = 0.13, P<0.001, respectively); while two studies [24, 27] were in the contrary (P>0.05, P<0.01, respectively); and one study [22] reported the two groups had the same operative time (P = 0.92) (Table 2). Therefore, the result of operative time was inconclusive.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the result of operative time was inconclusive. As only two [24, 27] from the five studies [21, 22, 24, 27, 28] reporting operative time were suitable for the meta-analysis, and the heterogeneity was substantial (Q statistic = 11.60, P = 0.0007; I 2 = 91%), we only made a qualitative systematic review for it.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations